Resiliensi Akademik Mahasiswa Pasca-bencana: Korelasi antara Tingkat Stres dan Gaya Belajar Mahasiswa Fakultas Kedokteran : (Universitas Tadulako Pasca Gempa Bumi, Tsunami dan Likuifaksi di Kota Palu Tahun 2018) - Ahmad Syuaib; Muhammad Sabir; Tri Setyawati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Natural disasters, as events that cause stress, trigger feelings of insecurity, anxiety, fear, and interfere with mental health due to the physical, psychological, and material impacts they cause. The psychological impact of such disasters can affect students' academic resilience, especially in terms of their ability to absorb information and adapt to the learning process. This study aims to determine the correlation between stress levels and learning styles of students of the Faculty of Medicine, Tadulako University after the earthquake, tsunami, and liquefaction that hit Palu City in 2018. The design of this study is an observational analysis with a cross-sectional approach, and involves a sample of 189 students who were randomly selected. Data analysis was carried out using the Contingency Coefficient, considering that the research variables were in the form of nominal and ordinal categorical scales. The results of the study showed that there was a significant relationship between stress levels and the learning style of preclinical students. The majority of college students experience very heavy levels of stress when compared to other levels of stress. Reflective learning styles were found to be the most dominant learning style among students, with their tendency to analyze, plan, and reflect on learning materials before making decisions or actions. In addition, the study also revealed that students with very high levels of stress tend to have a reflective learning style, which indicates a link between their emotional experiences and the way they absorb and process information.